The modelled surface mass balance of the Antarctic Peninsula at 5.5 km horizontal resolution - J. M. van Wessem; S. R. M. Ligtenberg; C. H. Reijmer; W. J. van de Berg; M. R. van den Broeke; N. E. Barrand; E. R. Thomas; J. Turner; J. Wuite; T. A. Scambos; E. van Meijgaard (The Cryosphere, 2016)
This study presents a high-resolution (∼  5.5 km) estimate of surface mass balance (SMB) over the period 1979–2014 for the Antarctic Peninsula (AP), generated by the regional atmospheric climate model RACMO2.3 and a firn densification model (FDM). RACMO2.3 is used to force the FDM, which calculates processes in the snowpack, such as meltwater percolation, refreezing and runoff. We evaluate model output with 132 in situ SMB observations and discharge rates from six glacier drainage basins, and find that the model realistically simulates the strong spatial variability in precipitation, but that significant biases remain as a result of the highly complex topography of the AP. It is also clear that the observations significantly underrepresent the high-accumulation regimes, complicating a full model evaluation.